Rezensionen / Book Reviews - Margit Schratzenstaller; Kai Eicker-Wolf; Torsten Niechoj; Wolfram Elsner; Eckhard Hein (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2007)
Rezension von: Corneo, Giacomo (2006): New Deal für Deutschland, Frankfurt a. M./New York Truger, Achim (Hg.) (2006): Die Zukunft des deutschen Steuersystems, Marburg Hödl, Erich (Hg.) (2006): Aspekte einer europäischen Wirtschaftsordnung, Marburg Hayden, F. Gregory (2006): Policymaking for a Good Society. The Social Fabric Matrix Approach to Policy Analysis and Program Evaluation, New York Trigg, Andrew B. (2006): Marxian Reproduction Schema. Money and Aggregate Demand in a Capitalist Economy, London/New York
Keywords: 330